PENINGKATAN EFEKTIVITAS PENYUSUNAN LAPORAN KEUANGAN SEDERHANA BAGI HIMPUNAN PENGUSAHA LAUNDRY INDONESIA (HIPLI) - Deni Darmawati; Shafrani Dizar; Cicely Delfina Harahap (Jurnal Berdaya Mandiri, 2020)
Accounting is an information system that generates financial statements used by relevant parties to report their economic activities and financial conditions. Many small Medium Enterprises (SMEs), the support of the nation's economy to date, still have not implemented accounting in conducting their businesses. This activity aims at improving the understandings and competencies of the laundry-business owners in applying simple financial statements and identifying challenges. Therefore, the accounting study Program in cooperation with the community of Laundry Entrepreneurs (HIPLI) implements a public service program, namely "Simple Financial Statements preparation training for the Association of Laundry Indonesia (HIPLI)". The results of this activity show that the relevant parties, such as governments, accountant profession organizations, educational institutions can motivate, facilitate and support the SMEs to compile their own financial report.